Palm Trees, Queen's Park Savannah, Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
The postcard shows some stately palms located in the Queen's Park Savannah in Port of Spain, Trinidad.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Mountains--Trinidad and Tobago; Savannas--Trinidad and Tobago; Palms--Trinidad and Tobago; Trees--Trinidad and Tobago; Benches--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spai; [1900]; Queen's Park Savannah (Port of Spain)